In vitro activity of amikacin against isolates of Mycobacterium avium complex with proposed MIC breakpoints and finding of a 16S rRNA gene mutation in treated isolates - Brown-Elliott, Barbara A; Iakhiaeva, Elena; Griffith, David E; Woods, Gail L; Stout, Jason E; Wolfe, Cameron R; Turenne, Christine Y; Wallace, Jr, Richard J (Journal of clinical microbiology, 2013)
Amikacin is a major drug used for the treatment of Mycobacterium avium complex (MAC) disease, but standard laboratory guidelines for susceptibility testing are not available. This study presents in vitro amikacin MICs for 462 consecutive clinical isolates of the MAC using a broth microdilution assay. Approximately 50% of isolates had amikacin MICs of 8 μg/ml, and 86% had MICs of ≤16 μg/ml. Of the eight isolates (1.7%) with MICs of 64 μg/ml, five had an MIC of 32 μg/ml on repeat testing. Ten isolates (2.1%) had an initial amikacin MIC of >64 μg/ml, of which seven (1.5%) had MICs of >64 μg/ml on repeat testing. These seven isolates had a 16S rRNA gene A1408G mutation and included M. avium, Mycobacterium intracellulare, and Mycobacterium chimaera. Clinical data were available for five of these seven isolates, all of which had received prolonged (>6 months) prior therapy, with four that were known to be treated with amikacin. The 16S mutation was not detected in isolates with MICs of ≤64 μg/ml. We recommend primary testing of amikacin against isolates of the MAC and propose MIC guidelines for breakpoints that are identical to the CLSI guidelines for Mycobacterium abscessus: ≤16 μg/ml for susceptible, 32 μg/ml for intermediate, and ≥64 μg/ml for resistant. If considered and approved by the CLSI, this will be only the second drug recommended for primary susceptibility testing against the MAC and should facilitate its use for both intravenous and inhaled drug therapies.